The Phonic Inventories: Using spelling error patterns to identify children with potential learning difficulties - Grasko, Dina Nicole (My University, 2008)
The Phonic Inventories are an instrument consisting of three spelling tests. This study explored the potential of this instrument to be used in group administration to identify children with potential learning difficulties. This was done with a sample of full-time mainstream and full-time remedial learners. A repeated measures ANOVA was used to establish if the Phonic Inventories could distinguish the spelling error patterns of learners in different grades for mainstream and remedial. A distinct pattern of key errors was found, which was similar for mainstream and remedial learners. There were performance changes over grade for mainstream learners but not for remedial learners. This suggests the Phonic Inventories may be measuring an underlying spelling ability which progresses in normal learners and not remedial learners. A stepwise regression analysis was used to establish whether the Phonic Inventories predict performance on contrast spelling tests. A good degree of fit was found between the tests, suggesting the Phonic Inventories are measuring the same abilities as other spelling tests, with the advantage of providing additional information. Finally, a discriminant analysis found errors made on the Phonic Inventories to predict group affiliation between the mainstream and remedial group to a good degree. It was concluded that the Phonic Inventories have strong potential as a group administered screening instrument for identifying children with potential learning difficulties.
Keywords: phonic errors; learning disability; phonological awareness; reading; writing; spelling ability